2006
DOI: 10.1038/sj.ki.5001607
|View full text |Cite
|
Sign up to set email alerts
|

Association between residence location and likelihood of kidney transplantation in Aboriginal patients treated with dialysis in Canada

Abstract: For reasons that are not well understood, Aboriginal people with end-stage renal disease (ESRD) have lower rates of kidney transplantation. We hypothesized that distance between residence location and the closest transplant center was greater in Aboriginal dialysis patients and would partially explain the lower rate of transplantation in this population. We studied a random sample of 9905 patients initiating dialysis in Canada between 1990 and 2000. We calculated the distance between residence location at dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 22 publications
0
36
1
3
Order By: Relevance
“…One Canadian study noted that approximately 24% of chronic dialysis patients live more than 150 km (93 miles) from the nearest available nephrologist (6). Distance from available nephrologists has been associated with poorer health outcomes (7)(8)(9). The goal of any chronic dialysis program is to provide optimal equitable care to all of its patients regardless of location and physician resources.…”
mentioning
confidence: 99%
“…One Canadian study noted that approximately 24% of chronic dialysis patients live more than 150 km (93 miles) from the nearest available nephrologist (6). Distance from available nephrologists has been associated with poorer health outcomes (7)(8)(9). The goal of any chronic dialysis program is to provide optimal equitable care to all of its patients regardless of location and physician resources.…”
mentioning
confidence: 99%
“…Assuming that improving access to nephrology care by reducing travel time would lead to improved outcomes and lower hospitalization rates, as suggested by observational studies (1)(2)(3)(4)(5)(6)(7)(8)(9), establishing this additional clinic would represent good value for money, with ICURs ranging from $4000 to $8000/QALY in most scenarios. However, if reducing distance to specialized care does not reduce the risk of hospitalization or mortality, the cost-effectiveness of establishing a new clinic may be considerably less attractive-although it still might be economically attractive by current standards.…”
Section: Discussionmentioning
confidence: 99%
“…Although kidney disease occurs throughout the province, specialized renal care is provided in 17 clinics that are predominantly located in the more densely populated southern half of Alberta ( Figure 1). Multiple studies (1)(2)(3)(4)(5)(6)(7)(8)(9) have shown that distance from health services is inversely associated with clinical benefits. We recently showed (10) that markers of good-quality care in CKD patients in Alberta decreased with increasing distance from the practice location of the closest nephrologist.…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has witnessed increased use of geographic information systems (GIS) analysis for measuring access to health services and facilities, healthcare utilization, and relationships with healthcare outcomes (6,7,9,12,(21)(22)(23)(24). However, the use of GIS techniques to determine the optimal location of a healthcare facility with the goal of optimizing patient access is limited (12,18,20,25).…”
Section: Introductionmentioning
confidence: 99%
“…Residents of remote communities may experience increased morbidity and mortality because of chronic diseases such as cardiovascular disease, chronic kidney disease (CKD), and cancer (1)(2)(3)(4)(5)(6)(7)(8)(9). Increased travel time to receive specialty care for such illnesses is a potentially reversible determinant of adverse outcomes, and several studies have shown that increased distance between the patient's residence and the closest relevant medical specialist is associated with adverse outcomes (9 -12).…”
Section: Introductionmentioning
confidence: 99%